Documenting legal status: a systematic review of measurement of undocumented status in health research - Maria-Elena De Trinidad Young; Daniel S. Madrigal (Frontiers Media S.A., 2017)
Abstract Background Undocumented status is rarely measured in health research, yet it influences the lives and well-being of immigrants. The growing body of research on undocumented status and health shows the need to assess the measurement of this legal status. We discuss the definition of undocumented status, conduct a systematic review of the methodological approaches currently taken to measure undocumented status of immigrants in the USA, and discuss recommendations for advancement of measurement methods. Methods We conducted a systematic review of 61 studies indexed in PubMed, conducted in the USA, and published from 2004 to 2014. We categorized each of the studies' data source and type, measurement type, and information for classifying undocumented participants. Studies used self-reported or proxy measures of legal status. Results Information to classify undocumented participants included self-reported status, possession of a Social Security number, possession of health insurance or institutional resources, concern about deportation, and participant characteristics. Findings show it is feasible to collect self-reported measures of undocumented status. Conclusions We recommend that researchers collect self-reported measures of undocumented status whenever possible and limit the use of proxy measures. Validated and standardized measures are needed for within and across country measurement. Authors should provide methodological information about measurement in publications. Finally, individuals who are undocumented should be included in the development of these methodologies. Trial registration This systematic review is not registered.